Support of Tunnels in South African Gold Mines - L. Z. Wojno (International Conference on Ground Control in Mining, 1987)
Tunnels in South African gold mines are developed at depths down to 3 600 m below surface where the virgin rock stress approaches 100 MPa and, on occasions, through rock where the field stresses exceed 150 MPa. In addition, many tunnels are subjected to increases in field stress of over 50 MPa during their useful lifetime. As a consequence, the walls of most tunnels are fractured causing the rock to dilate into the tunnel. Quantitative data on the extent of this fractured zone are presented. The function of support in these circumstances is to reinforce and maintain the integrity of the fractured rock. In 80 per cent of the 800 km of tunnels developed annually, the support methods used are capable of maintaining the stability of the tunnels. However, the remaining 20 per cent of tunnels is subjected to severer conditions where dilation in excess of 250 mm occurs and/or where the probability of strong seismic ground motion is high. In these tunnels, additional support is required. The type and pattern of support for both normal and severe conditions is described. In spite of the improved support used, damage to tunnels may occur. To minimize this damage, the concept of a rock reinforcing tendon that will yield and do work, when subjected to quasi-static or rapid deformation, has been put forward. Specifications for such a tendon are presented and the development of certain yielding tendons are described.